The Multi Soil layering Method for Wastewater Treatment: Review - Rahayu, Aster; Mulyadi, Irwan; Fajri, Joni Aldilla; Jamilatun, Siti Jamilatun; Nuraini, Nuraini; Wulandari, Nurul; Marlena, Yuni; Ningsih, Devi Yogi Noviana; Lim, Lee Wah (Indonesian Journal of Chemical Research, 2022)
Liquid waste is the main source of contamination of water bodies, especially river water. This pollution causes decreased water quality in water bodies. One of the wastewater treatment treatments is the Multi Soil Layering (MSL) method. Some of the advantages of using the MSL method are that it is known to be cheap in terms of cost, easy to implement, does not require complicated maintenance so that it can be used continuously, and is also environmentally friendly. One of the constituent materials of the MSL reactor is andesol soil, gravel, and pearlite. MSL has two wastewater treatment zones, the aerobic zone, and the anaerobic zone. The article review aims to compare the efficiency of reducing the levels of pollutant parameters from aerobic and anaerobic processes in MSLmethod in wastewater.